PERLINDUNGAN HUKUM TERHADAP KEBOCORAN DATA PRIBADI OLEH PENGENDALI DATA MELALUI PENDEKATAN HUKUM PROGRESIF - Herol Hansen Samin (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study aims to analyze the legal protection against personal data breaches by data controllers and to conceptualize efforts to optimize such legal protection through a progressive legal approach. The method used is normative legal research, which involves literature study and analysis of legal behavior products, including laws and other legal documents relevant to personal data protection issues. This research examines the principles of law, legal doctrines, and legal developments related to personal data protection, as well as conducting comparative and historical analysis to understand the existing legal dynamics. The findings indicate that personal data breaches are a serious challenge in the digital era, and there are currently deficiencies in existing policies and regulations, especially regarding the responsibility of data controllers and victim protection. This research highlights the need for a more flexible and human rights-oriented progressive legal approach, as well as increasing public awareness of data privacy.